2021
DOI: 10.1007/s13530-021-00118-1
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and anticancer activity of a novel synthesized tet-AuNPs simultaneously activates p53 and inhibits NF-kB signaling in SKBR3 cell line

Abstract: Objective The objective of this study was to synthesize novel gold nanoparticles (Au(0)NPs) that simultaneously activates p53 and inhibits NF-kB signaling in SKBR3 breast cancer cells. Methods The tetracycline-based Au(0)NPs were synthesized by chemical method. These Au(0)NPs were characterized by different authentic techniques. The first characterization technique was UV-Visible (UV-Vis) spectroscopy to monitor Plasmon absorption maxima at 529 nm. The second technique was X-ray powder diffraction (XRD) patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The NF-κB family includes critical transcription factors that are activated by various stimuli, including TNF-α, IFN-γ, and LPS. Upon stimulation, NF-κB complexes in the cytoplasm translocate to the nucleus, where they participate in the expression of numerous proinflammatory genes [ 36 , 37 ]. NF-κB signaling pathways are involved in the regulation of proinflammatory cytokines, such as IL-6, IL-8, and IL-1β, and chemokines, including TARC and MDC in HaCaT cells [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The NF-κB family includes critical transcription factors that are activated by various stimuli, including TNF-α, IFN-γ, and LPS. Upon stimulation, NF-κB complexes in the cytoplasm translocate to the nucleus, where they participate in the expression of numerous proinflammatory genes [ 36 , 37 ]. NF-κB signaling pathways are involved in the regulation of proinflammatory cytokines, such as IL-6, IL-8, and IL-1β, and chemokines, including TARC and MDC in HaCaT cells [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that IFN-γ and TNF-α can activate NF-κB, which is responsible for the expression of pro-inflammatory chemokines and cytokines [ 42 ]. Among these cytokine stimuli, IκB proteins are phosphorylated and degraded, which allows the translocation of NF-κB into the nucleus, where it can bind to specific promoter regions of target genes and activate the expression of inflammatory-cytokine genes [ 43 ]. Thus, the inhibition of NF-κB activation plays a key anti-inflammatory role in AD.…”
Section: Discussionmentioning
confidence: 99%
“…Using controlled and sequenced release mechanisms to prevent undesirable outcomes associated with simultaneous codelivery, local DDSs can restrict drug–drug interactions, improve therapeutic effectiveness, and minimize drug resistance in skin cancer treatment. The field of sequential and on-demand DDSs has seen a growth in the development of responsive biomaterials with configurable physical and chemical characteristics. Because of their reversible phase transformation in reaction to stimulation and physiochemical influences such as pH, temperature, and enzymatic activity, and external forces such as UV light, near-infrared (NIR), ultrasound, electric, and magnetic radiation, these materials can be used as drug-carrier frameworks for the effective delivery of pharmaceuticals. Because most drugs must be given repeatedly and consistently over long periods of time to be effective, and their concentrations must remain within the desired effective range to prevent overuse or underdosing, it is necessary to develop and improve new adaptive systems that can be easily controlled externally and capable of being spatially programmed. ,, …”
Section: Introductionmentioning
confidence: 99%